Somatotype and performance in female futsal players - Gleber Pereira; Sandra Aires Ferreira; Marcos Queiroga; Eduardo Kokubun (Universidade Federal de Santa Catarina, 2008)
The present study aimed to verify whether body somatotype was indicative of competitive success in female utsal (indoor soccer) players. One hundred and twelve players (22.1 ± 5.4 years; 58.4 ± 6.9 kg; 161.8 ± 6.2 cm), from ten teams and seven different states, had participated in a national competition. The anthropometric date was analyzed using one-way ANOVA for repeated measures. The somatotype dispersion distance was applied to compare somatotypes between the champion team (reference) and the other teams (from 2nd to 10th position). Anthropometric characteristics didnot differ signifi cantly among teams. The results showed that the endomorphic component was predominant in relation to the mesomorphic and ectomorphic component, irrespective of a team's ranking at the end of the competition. Therefore, the body somatotypes of female futsal teams cannot be considered as indicative of their competitive success. Resumo O presente estudo teve como objetivo verificar se o somatotipo corporal pode ser considerado um indicador de desempenho em atletas de futsal feminino, levando em consideração a classifi cação das equipes em uma competição ofi cial. A população foi constituída de 112 jogadoras (22,1 ± 5,4 anos; 58,4 ± 6,9 kg; 161,8 ± 6,2 cm), pertencentes a dez equipes de sete estados que disputavam a competição. Os dados antropométricos foram analisados mediante ANOVA one-way para medidas repetidas. Para comparar o somatotipo da campeã (referência) com o das demais classificadas (2ª a 10ª colocação) na competição, recorreu-se ao cálculo da distância de dispersão do somatotipo. As características antropométricas das equipes não diferiram estatisticamente. Os resultados revelaram que a endomorfia foi predominante em relação à mesomorfia e ectomorfia, independente da classificação das equipes na competição. Neste caso, a classifi cação somatotipológico apresentada pela equipe vencedora, ou qualquer outra neste estudo, não deve ser considerada indicadorde desempenho no futsal feminino.